(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article indicates the need for a proper approach to the development of preschool children’s speech using modern gaming technologies. The author of the article strongly emphasizes that the formation of grammatically correct, lexically rich and phonetically pure speech in children is one of the most important tasks in the general system of upbringing and education of a child.